Application of Six Sigma for evaluating the analytical quality of tumor marker assays. Issue 2 (2nd October 2018) - Liu, Qian; Fu, Mei; Yang, Fumeng; Liang, Wei; Yang, Chuanxi; Zhu, Wenjun; Ma, Liming; Zhao, Changxin
Abstract : Context: The results of detection assays for the same specimen are usually quite different in different laboratories or when tested with different detection systems. Objective: This study was designed to investigate the value of applying sigma metrics derived from different standards for allowable total error (TEa) in evaluating the analytical quality of tumor marker assays. Methods: Assays were evaluated for these six tumor markers: total prostate‐specific antigen (tPSA), carcinoembryonic antigen (CEA), alpha‐fetoprotein (AFP), carbohydrate antigen 199 (CA199), carbohydrate antigen 125 (CA125), and carbohydrate antigen 153 (CA153). Sigma values were calculated for two concentrations of quality control products to assess differences in quality of tumor marker assays. Improvement measures were recommended according to the quality goal index, and appropriate quality control rules were selected according to the sigma value. Results: The sigma value was highest using the higher biological variation‐derived "appropriate" TEa standard: it was sigma ≥6 or higher in 16.7% of tumor markers. Sigma was below 6 for all tumor markers using the other three TEa. CEA, AFP, CA199, CA125, and CA153 required improved precision. The marker tPSA required improve precision and accuracy. According to sigma values by using China's external quality assessment standards, CEA, AFP, CA125, and CA153 require 13s /22s /R4s /41s multirules for internal quality control, CA199 requires use of 13s /22s /R4s /41s /8x multirules, and tPSA requires maximum quality control rules. Conclusion: Six Sigma is useful for evaluating performance of tumor markers assays and has important application value in the quality control of these assays.